(untitled) (Jurnal Simki Postgraduate, 2023)
The Influence of the Principal’s Democratic Leadership Style on Teacher Work Productivity at Mts Darunnajah 2 Cipining Bogor, Thesis, Islamic Education Management Study Program, Darunnajah Islamic College Bogor, 2022. This research was conducted with the aim of finding out how much the Principal’s Democratic Leadership Style has on Productivity Teacher Work at Mts Darunnajah 2 Cipining Bogor, Thesis, Islamic Education Management Study Program. This research approach uses a quantitative approach with survey methods and questionnaires or questionnaires. The population in the study were MTs teachers, totaling 44 teachers. The instrument of this study was a democratic leadership style questionnaire, totaling 30 statement items for the variable library facilities, while for the teacher’s work productivity variable, there were 30. After the trial was carried out, it was declared valid as many as 17 statement items for the teacher productivity variable, totaling 11 statement items, then used for decision making. data. Then the normality test and simple regression were carried out. Based on the results of the study, it was found that the correlation coefficient was 0.503. This indicated that there was a correlation between the democratic leadership style and the work productivity of student teachers with high criteria (0.60-0.799). This is supported by a coefficient of determination of 50.3%, while 49.7% is influenced by other factors.